“Evaluación del rendimiento de tres cultivares de arroz, mediante diferentes programas de fertilización edáfica en la zona de Pimocha”. - ARANA VACA, DIEGO ARMANDO (2019)
VIII. SUMMARY The present experimental work was established in the lands owned by Mr. Eugenio Arana Quinto, located in the Rcto. "La Ángela", belonging to the Pimocha parish, between the geographic coordinates of 110597.97 UTM of South latitude and 277438.26 UTM of West longitude, with a height of 8 m.s.n.m. The zone presents a humid tropical climate, with an average temperature of 25.60 ° C; an annual rainfall of 2298.8 mm, humidity 82% and 998.2 hours of annual average heliophany. The soil has a flat topography, a loamy clay texture and regular drainage. As seed material and treatments were used rice seeds, Iniap FL 1480 Cristalino, Iniap 15 and SFL 11 varieties and as sub-treatments Edaphic Fertilization Programs according to soil analysis results, according to the requirements of the crop (150 kg / ha of N - 40 kg / ha of P2O5 - 40 kg / ha of K2O and conventional (160 kg / ha of Nitrogen) The experimental design of divided plots was used, with three treatments, three sub-treatments and four repetitions The variables evaluated were subjected to the analysis of variance, using the test of significance of Tukey at 95% probability for comparisons of the means of treatments.All the necessary agricultural work was done in rice cultivation for its normal development as soil analysis, land preparation, sowing, irrigation, fertilization, weed control and phytosanitary and harvesting, based on the results obtained, it was determined that sowing the rice variety I ndia SFL 11 for presenting greater performance in the present investigation; apply fertilization programs according to the requirements of the crop (150 kg / ha of N - 40 kg / ha of P2O5 - 40 kg / ha of K2O), to obtain greater net benefit and increase the yields of the rice cultivation and make a replica of the trial in another location to compare their results. Keywords: rice, fertilization, rice varieties.